Numerical simulation of the tension–compression behavior of tie connections in brick masonry walls - Ortega, Javier (2022)
Brick masonry veneer walls connected to infill walls inserted in a reinforced concrete (RC) frame are a common constructive system in Portugal. The stability of the veneer wall is ensured by ties that make the connection with the masonry infill walls. These ties enable the transferring of out-of-plane loads to the main structure due to wind, and particularly due to earthquakes. However, the characterization of the seismic behavior of these tie connections is an insufficiently explored topic. The present paper shows a numerical investigation that aims to simulate experimental results of tension and compression tests performed on masonry prisms connected by means of steel ties. The main objective of the present research is to obtain a better understanding of the complex structural behavior of this specific construction system to then develop simplified numerical tools to be used in engineering practice for the seismic design and retrofitting of brick masonry veneer walls. The numerical results match well the experimental ones, and the validated approach can be used in the future to carry out parametric analyses to evaluate the influence of material and geometric properties of the tie and masonry, as well as the type of action and construction details.